2013
DOI: 10.1182/blood-2012-09-456038
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the A3 domain of Von Willebrand factor inducing combined qualitative and quantitative defects in the protein

Abstract: Key PointsVWF A3 domain mutations inducing defective collagen binding and impaired protein production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…This result raised the possibility that the mutant protein was cleared more rapidly than wild-type VWF in vivo , a feature that cannot be detected in vitro . Mice expressing the second A3 domain mutant, p.P1824H-VWF also displayed low expression VWF levels, but the probable underlying cause, intracellular retention was this time detected both in the in vitro and the in vivo expression systems 41. For both mutants, the thrombotic response in arterioles of mice was strongly decreased, but the low expression levels did not allow concluding as whether this effect should be attributed to the quantitative defect or to the qualitative defect.…”
Section: Analysis Of Mice Reproducing Different Subtypes Of Human Vwdmentioning
confidence: 96%
See 1 more Smart Citation
“…This result raised the possibility that the mutant protein was cleared more rapidly than wild-type VWF in vivo , a feature that cannot be detected in vitro . Mice expressing the second A3 domain mutant, p.P1824H-VWF also displayed low expression VWF levels, but the probable underlying cause, intracellular retention was this time detected both in the in vitro and the in vivo expression systems 41. For both mutants, the thrombotic response in arterioles of mice was strongly decreased, but the low expression levels did not allow concluding as whether this effect should be attributed to the quantitative defect or to the qualitative defect.…”
Section: Analysis Of Mice Reproducing Different Subtypes Of Human Vwdmentioning
confidence: 96%
“…As mentioned earlier, only murine VWF is hemostatically active in the mouse, preventing use of human VWF. However, since we had generated an active human-murine VWF chimera (hVWFmA1) in order to test the anti-thrombotic effect of monoclonal antibodies inhibiting specific VWF functions,24 we also used the same construct to introduce VWF mutations present in the A3 domain and detected in patients with VWD 41. Mutations in the VWF A3 domain have not been described as frequently as mutations in the platelet-binding domain (the A1 domain) but they are now being increasingly recognized 4244.…”
Section: Analysis Of Mice Reproducing Different Subtypes Of Human Vwdmentioning
confidence: 99%
“…The A3 domain is able to interact with various types of collagen, including collagens I & III, and the complementary binding sequences in collagen I and III have been deciphered in detail 8285. The importance of the A3 domain in binding to collagen is supported by the finding that mutations in or around the collagen binding site may be associated with an increased bleeding tendency 86–89…”
Section: The Classical Functions Of Vwf: Collagen Bindingmentioning
confidence: 99%
“…The standard functional assays for VWD detection do not always evaluate the collagen-binding function of VWF (VWF:CB), and assays for diverse collagen types are even less common, which may have contributed to the scarcity of reported VWF:CB deficiencies [3]. Functional and molecular studies focused on this VWF dysfunction have increasingly reported VWF sequence variations that affect the ability of VWF to bind type I, type III and type VI collagen [3][4][5][6]. However, some of these mutations may not interfere with the screening assays, which show normal values, and can only be detected using type VI collagen.…”
mentioning
confidence: 99%
“…First, the well-characterized mutation that involved the same hydrophobic linear amino acids (p.Ala1716Pro) was associated with type 1 VWD, although this association was based solely on the VWF: Ag and VWF:RCo levels [10]. Second, one study described two mutations in the A3 domain that led to a combined qualitative and quantitative defect in VWF that exhibited decreased binding to collagen (types I and III) and the platelet glycoproteins Ib and IIb-IIIa [6].…”
mentioning
confidence: 99%